Analisis Kadar Yodium pada Garam yang Diproduksi di Kecamatan Labakkang Kabupaten Pangkep - Nardin Nardin; Yunita Wandira (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Iodized salt is salt that has been enriched with iodine which is very important for the body. Iodized which is used as consumption must comply with the Indonesian National Standard (SNI) that has been set. The purpose of this study was to determine the iodine content contained in salts produced in Labakkang District, Pangkep Regency in 2018. The type of research used was descriptive by giving an overview of iodine levels (KIO3) in salt with a population of all salt sellers in Labakkang District, Pangkep Regency using five samples with sampling techniques, namely purposive sampling conducted with qualitative tests and quantitative tests on August 24, 2018 at the Pharmacy Laboratory of the University of East Indonesia. The results of laboratory tests on iodine levels in salt with a qualitative test showed positive results in all samples and quantitative tests obtained iodine content that in sample C the iodine content was in accordance with SNI standards. In sample B and sample E approaching from the established SNI standard while in samples A and D are far below the SNI standard. Based on the results of the study, it can be concluded that iodine content in salts produced in Labakkang sub-district, Pangkep regency is only 1 sample that meets SNI standards, namely 30-80 ppm.